2019
DOI: 10.1002/sys.21490
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory development processes for reducing total ownership costs and schedules

Abstract: Many systems and software processes overfocus on getting a project and product from an initial set of requirements to an Initial Operational Capability (IOC). Examples are most waterfall and V models. Projects following such processes may pass acceptance tests for functionality and performance, but may leave the product with serious maintainability shortfalls. Many agile processes focus on users' initial usage priorities, but often make development commitments for earlier needs that are incompatible with achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…21 Boehm and Behnamghader identified process and non-technical sources of technical debt affecting program schedule, including undisciplined software development approaches and inadequate systems engineering resources. 22 Tate argued that DoD programs are increasingly software dependent and that Agile development could deliver products on reduced timelines. 5 Forney found that while larger unit size and less development work increased the likelihood of schedule success, Agile software development methods did not increase success likelihood.…”
Section: Agile Development and Dod Program Managementmentioning
confidence: 99%
“…21 Boehm and Behnamghader identified process and non-technical sources of technical debt affecting program schedule, including undisciplined software development approaches and inadequate systems engineering resources. 22 Tate argued that DoD programs are increasingly software dependent and that Agile development could deliver products on reduced timelines. 5 Forney found that while larger unit size and less development work increased the likelihood of schedule success, Agile software development methods did not increase success likelihood.…”
Section: Agile Development and Dod Program Managementmentioning
confidence: 99%
“…show that poor documentation leads to increased maintenance costs and effort in software and hardware systems and component obsolescence is a concern in both fields 12 . Boehm and Behnamghader discuss how inadequate systems engineering resources can lead to “exponentially‐large amounts of TD due to poorly‐defined interfaces, unaddressed rainy‐day use cases and risks, and premature commitments to hopefully‐compatible but actually‐incompatible COTS products, cloud services, open‐source capabilities, and hopefully‐reusable components.” 13 Sharon et al. correlate systems engineering management and project management and identify that “careful management of the relationships between the product and the project is crucial to the successes of a project that aims to deliver a defined product.” 14 These sources all discuss critical elements of technical debt—unintended consequences, the impact of early decisions on the long‐term health of the system, and the need for adequate resourcing and careful decision‐making.…”
Section: Introductionmentioning
confidence: 99%